The relationship between antibrowning, anti-radical and reducing capacity of Brassica and Allium extracts - Bustos Shmidt, Mariela Cecilia (2014)
Aqueous vegetable extracts from Allium and Brassica families were assayed for antibrowning capacity and related to their anti-radical and reducing power activities. The treatment of mushrooms and avocado slices, with white cabbage, cauliflower, garlic and scallion extracts, reduced color changes during storage at 4 °C and -18 °C. Storage temperature and the type of extract employed influenced change of color variables. The contribution of polyphenols on measured antioxidant activity of extracts was also discussed. Allium antibrowning properties were closely related to antioxidant capacity, while the Brassica extracts were less effective. Treatment with Allium extracts extended the storage time of frozen and refrigerated mushrooms and avocado slices, in comparison with untreated samples.